ANTIRADICAL ACTIVITY AND DETERMINATION OF PHENOLIC COMPOUNDS OF EXTRACTS OF LIPPIA MULTIFLORA (VERBENACEAE): A PLANT TRADITIONALLY USED AGAINST ARTERIAL HYPERTENSION IN BENIN - Gandonou, Clément; TOKOUDAGBA, Kossi Jean-Marie Denis; Ahissou, H. (My University, 2018)
The antiradical potential of Lippia multiflora evaluated by the DPPH radical method reveals that the hydroethanolic extract has a higher antioxidant capacity (957.90 ± 2.42 mmolEAA / mg) than the aqueous extract (489.35 ± 11.29 mmol EAA / mg) against 14.43 mg / mL for ascorbic acid used as reference antioxidant. The contents of the phenolic compound extracts have been determined and vary according to the extract. These values are between be 104.68-957.90% 957.90% for total phenols, 0.038 0.038-0.338% for flavonoids and 0.002-0.031% 0.002 0.031% for condensed tannins. The hydroethanolic extract has high levels of these metabolites irrespective of the area of origin of the plant, which would justify their strong an anti-radical activity
Keywords: Lippia multiflora; Extract; Anti-radical; Activity; Phenolic compounds.